Peningkatan Keterampilan Menulis Deskripsi melalui Model Pembelajaran Kreatif pada Siswa Kelas Va SDN 1 Labuhan Ratu Bandar Lampung Tahun Pelajaran 2022/2023 - Marhedah, Marhedah (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
This study aims to improve the skills of writing Indonesian language descriptions in fifth grade students of SD Negeri 1 Labuhan Ratu semester 1 of the 2022/2023 school year by applying a creative learning model. This research is a Classroom Action Research (PTK) which consists of two cycles. The research subjects were fifth grade students at SD Negeri 1 Labuhan Ratu, Bandar Lampung. The data collection technique used is the test and nontes technique. Data analysis used descriptive comparative analysis techniques to process quantitative data, namely data obtained in pre-cycle, cycle I, and cycle II were compared to determine an increase in the learning outcomes. The results of this study indicate that the application of creative learning models can improve descriptive writing skills.